Activation of brain macrophages/microglia cells in hepatitis C infection. Issue 10 (30th July 2010) - Wilkinson, Jeffrey; Radkowski, Marek; Eschbacher, Jennifer M; Laskus, Tomasz
Abstract : Objectives: Hepatitis C virus (HCV) infection is commonly associated with cognitive dysfunction. Viral sequences and proteins were previously found in brain macrophage/microglia cells. The aim of the current study was to determine whether HCV infection affects the expression of key cytokines and chemokines in these cells. Methods: Autopsy brain tissue from 15 patients was studied; 7 patients were HCV positive and 8 were HCV negative. Cryostat sections of frontal cortex and subcortical white matter were stained with monoclonal antibodies specific for microglia/macrophages (anti-CD68) and separated by laser capture microscopy. Transcripts representing 25 various cytokines and chemokines were measured by real-time quantitative PCR. Results: Compared with HCV-negative controls, HCV-positive patients demonstrated significantly higher levels of proinflammatory cytokines interleukin 1α (IL-1α), IL-1β, tumour necrosis factor α (TNFα), IL-12 and IL-18. HCV infection was also associated with increased transcription of chemokines IL-8, IL-16 and interferon-inducible protein 10 (IP-10). Type 1 interferon (IFN) activation was suggested by increased concentrations of IFNβ and myxovirus resistance protein A (MxA) transcripts. Similar results were obtained when CD68-positive/HCV-positive cells were compared with CD68-positive/HCV-negative cells in each of the 7 HCV-infected patients. Conclusion: Evidence was found for activation of brain macrophages/microglia cells in autopsy brain tissue from HCV-positive patients. These findings could relate to the common presence of neurocognitive dysfunction among patients with chronic hepatitis C.